Feminism in the Novel "Jane Eyre" by Charlotte Brönte - Widya Firmanilla Mentari (Lexicon, 2014)
The research objective is to find out the ideas opposed by Feminism depicted in the novel Jane Eyre written by Charlotte Bronte. The object of the research is the main character in the Novel, Jane Eyre, as the focus of the study or limit of the research. In analyzing the object of the study, the research employs the liberal feminism theory proposed by Allison M. Jaggar. The theory applied that woman as well as man had natural rights. In fact, there are inequality that woman faces. They are man domination, inequality of education, inequality in occupation and the ownership right. The research attempts to give evidence about Jane Eyre’s effort to be an independent woman. Based on the story of Jane Eyre in the novel, the result proves that Jane Eyre is a representation of the liberal feminism.